Issues and development for an automated welding station using robotic arm - Pan, Deng (2014)
In this report, two issues about robotic welding are addressed. One is about welding accessibility or collision-free path planning of welding robot (by Pan Deng), while the other is about cost modeling of robotic welding (by Gu Jiayin).